RAMUAN OBAT TRADISIONAL SUB-ETNIS BATAK KARO YANG DIPERJUALBELIKAN DI PASAR BERASTAGI DAN KABANJAHE SUMATERA UTARA - Silalahi, Marina (Jurnal Ilmiah Kesehatan Keperawatan, 2019)
Research has been carried out on the ingredients of traditional Batak Karo medicine which are traded in the Berastagi and Kabanjahe traditional markets, North Sumatra. The study was conducted through an ethnobotany approach. The survey was conducted with free interviews, in-depth, semi-structured, and participatory observations to all traditional medicinal herb traders in the Berastagi and Kabanjahe traditional markets. The local name of the ingredients, benefits, form of packaging, plants, and how to use each ingredient is asked to the trader. In the Berastagi and Kabanjahe traditional markets sold 20 types of traditional medicinal which are divided into parem, tawar and minyak urut (oil for massage). The trader sell 12-18 types of concoctions. The medicinal ingredients are used for more curative purposes than preventive purposes. The traditional ingredients found in this study are classified into herbs because their properties are based on empirical experience only.